Population Aging and Cross-Country Redistribution in Integrated Capital Markets - Thomas Davoine (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Population aging challenges the financing of social security systems in developed economies, as the share of the working age population declines. The resulting pressure on capital-labor ratios tends to push up factor prices and production. While European countries all face this challenge, the speed at which their populations are aging differs. If capital markets are integrated, differences in population aging may lead to cross-country spillovers, as investors freely seek the best returns on their capital. Using a multi-country overlapping-generations model covering 14 European Union countries, this paper quantifies spillovers and finds that capital market integration leads to redistribution across countries over the long run. It also shows that pension reforms can change the cross-country redistribution patterns, some countries losing from capital market integration without the reform but winning with it.
Keywords: 330